Seizing the moment: talking about the "undiscussables" - Baker, Ann C. (2004)
Given the varied backgrounds, experiences, and perspectives among students and faculty in management education and organizational studies programs, often teachable moments present themselves around differing perceptions. Seizing these moments to talk about difficult, controversial issues - or undiscussables - can catalyze and deepen learning. This article delves into the underutilized resource of class conversations for conversational learning. It explores how to prepare more receptive learning environments and how to prepare faculty to facilitate conversational interactions that can promote a more complex level of learning. The article concludes with two illustrations from actual classroom work. - Reproduced.
Keywords: Management education